2012
DOI: 10.1111/j.1600-051x.2012.01921.x
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of inter‐proximal and midfacial recession following single implant treatment in the anterior maxilla: a multivariate analysis

Abstract: To optimize soft tissue levels around single implants, clinicians should limit papilla-opening procedures and pay utmost attention to a correct implant and contact point positioning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
139
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(145 citation statements)
references
References 32 publications
6
139
0
Order By: Relevance
“…13,15 In order to identify predictors of gingival recession around single-tooth restorations in the anterior maxilla, it has been reported that only a buccal shoulder position of the implant (OR = 17.2) was associated with midfacial gingival resorption. 16 For interproximal tissues, ridge recontouring was associated with recession of both mesial (OR = 3.4) and distal (OR = 11.2) papillae. 16 In addition, mesial and distal papilla recession was associated with bone loss around a periodontally involved tooth that was mesial (OR = 2.1) or distal (OR = 2.7) to the implant itself, respectively.…”
Section: -14mentioning
confidence: 99%
See 2 more Smart Citations
“…13,15 In order to identify predictors of gingival recession around single-tooth restorations in the anterior maxilla, it has been reported that only a buccal shoulder position of the implant (OR = 17.2) was associated with midfacial gingival resorption. 16 For interproximal tissues, ridge recontouring was associated with recession of both mesial (OR = 3.4) and distal (OR = 11.2) papillae. 16 In addition, mesial and distal papilla recession was associated with bone loss around a periodontally involved tooth that was mesial (OR = 2.1) or distal (OR = 2.7) to the implant itself, respectively.…”
Section: -14mentioning
confidence: 99%
“…16 For interproximal tissues, ridge recontouring was associated with recession of both mesial (OR = 3.4) and distal (OR = 11.2) papillae. 16 In addition, mesial and distal papilla recession was associated with bone loss around a periodontally involved tooth that was mesial (OR = 2.1) or distal (OR = 2.7) to the implant itself, respectively. 16 In another study, Cosyn et al 17 utilized the Pink Esthetic Score 18 (PES) to evaluate the esthetic results of implants immediately placed and provisionally restored with single-tooth restorations after tooth extraction.…”
Section: -14mentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of healthy bone on adjacent tooth and the location of the contact point at a distance of 5 mm or less were determinant factors in Grunder's study. Although the differences established by different authors regarding the papilla position, its clear that a missing contact point, the implant-to-tooth distance and the distance of the bone peak to the contact point address as important predictors in terms of papilla recession, plus the surgical approach or flap design [30]. …”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that positioning the implant platform subcrestally is associated with greater crestal bone loss. [14][15][16] It also has been demonstrated that the vertical periimplant bone resorption increased from 0.78, preceding an abutment disconnection to 1.49 after 5 "insertions and removals." 11,12 This level of placement may compromise the long-term aesthetic results if crestal bone loss occurs around the implant.…”
mentioning
confidence: 99%